C59N+: A key intermediate in azaheterofullerene chemistry - Hauke, Frank; Hirsch, Andreas; Hauke, Frank (Tetrahedron, 2001)
The thermal treatment of the azaheterofullerene dimer (CN) in the presence of oxygen and a nucleophilic trapping reagent leads to the facile and selective formation of a variety of monomeric adducts CNR involving electronic rich aromatics, carbonyl compounds, alcohols and olefins as terminating addend. These investigations within the field of synthetic heterofullerene chemistry imply the presence of CN as an important key intermediate. © 2001 Elsevier Science Ltd.